The Influence of Career Development, Emotional Intelligence, and Affective Commitment on Employee Performance (Case Study of PT. Visi Insan Sukses Demak Branch). - Farah Humaidah; Indah rahayu (JMBPreneur: Jurnal Manajemen, Bisnis, dan Kewirausahaan, 2024)
Background: Competition in the industrial sector is currently very tight due to the increasing number of companies, especially in the city of Demak, so companies are required to improve the performance of their human resources through career development by providing additional training will make employees have a deep understanding of the company's goals and increase their affective commitment to the company so that employees feel happy to be able to contribute to the company. So that when working you will be more comfortable and be able to complete work on time and interactions at work will be more harmonious, which will improve employee performance.Purpose : Based on the background and problem formulation that has been explained, the aim of this research is to analyze and describe the influence of career development on employee performance, analyze and describe the influence of emotional intelligence on employee performance, analyze and describe the influence of affective commitment on employee performance.Method: This research uses a quantitative approach which aims to test the formulated hypothesis. The sample used in this research was 70 respondents with a saturated sampling technique where the entire population was sampled. Analyzed using Partial Least Square (PLS) statistical analysis technique version 4.0.Results: The research results show that career development has a positive and significant effecvbt on employee performance, emotional intelligence has a positive and significant effect on employee performance, affective commitment has a positive and significant effect on employee performance.Conclusion: So, career development, emotional intelligence, and affective commitment play a role in improving employee performance.Suggestion: In this research, the career development and emotional intelligence variables show that the results are in the moderate category for employee performance, but the affective commitment variable shows that the results are in the weak category for employee performance. Therefore, it is recommended that the future agenda be to develop variable measurements so that they can provide better results